Underutilized treatments for patients with refractory cancer pain: a qualitative study assessing the use of intrathecal drug delivery devices in the United Kingdom compared to alternative treatments in cancer pain management - Barnosky, Victoria; Brown, Matthew; Bagchi, Somnath; Blain, Remy; Husejnovic, Demir; Johnson, Sandra; Mackworth-Praed, Meredith (Frontiers in Pain Research, 2025)
ObjectivesThis research aims to better delineate how intrathecal drug delivery systems (IDDS) are incorporated into the oncology care continuum and highlight the need for further awareness of interventional options for pain management of cancer patients in the United Kingdom. The study focuses on exploring the knowledge, perspectives, and experiences of healthcare professionals regarding IDDS as a treatment option for managing chronic refractory pain in cancer patients.MethodologyA thematic coding using inductive analysis was employed to achieve the research objectives. Semi-structured interviews were conducted with 18 healthcare professionals in various specialties, including oncology, neurosurgery, pain management, and palliative care. The interviews were transcribed, and a two-phased qualitative inductive coding approach was used to analyze the data.ResultsThe findings of the study revealed four major themes: Education, Barriers & Benefits, Technical & Administrative, and Patient-Centered Care. The theme of Education highlighted the need for increased knowledge and awareness of IDDS among healthcare professionals. Barriers & Benefits encompassed concerns about infection risk, suitability for patients with a short life expectancy, and the challenges and advantages of IDDS use. The Technical & Administrative theme addressed cost considerations, device management, and the need for improved guidelines. Patient-Centered Care emphasized the importance of involving patients in decision-making and considering their physical and emotional well-being throughout the treatment pathway.ConclusionsThis research identifies several areas of unmet need in the management of refractory pain in cancer patients, including the development of more inclusive guidelines, greater awareness among clinicians and patients, and the role of medical technology companies in supporting effective pain management. The findings underscore the impact of IDDS on improving pain control and highlight the potential importance of early intervention and comprehensive pain management in influencing the trajectory of oncological diseases.